2017
DOI: 10.1016/j.ccell.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Accessibility Landscape of Cutaneous T Cell Lymphoma and Dynamic Response to HDAC Inhibitors

Abstract: Summary Here, we define the landscape and dynamics of active regulatory DNA in cutaneous T cell lymphoma (CTCL) by ATAC-seq. Analysis of 111 human CTCL and control samples revealed extensive chromatin signatures that distinguished leukemic, host, and normal CD4+ T cells. We identify three dominant patterns of transcription factor (TF) activation that drive leukemia regulomes, as well as TF deactivations that alter host T cells in CTCL patients. Clinical response to histone deacetylase inhibitors (HDACi) is str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(140 citation statements)
references
References 62 publications
7
133
0
Order By: Relevance
“…We speculate that this differential response to HDACi treatment is related to individual variation in chromatin accessibility. For example, in clinical studies testing the efficacy of HDACi drugs as cancer treatments, the pattern of transcription factor occupancy in cells from individual T‐cell lymphoma patients predicts HDACi treatment efficacy . In responsive patients, HDACi treatment is correlated with a rise in DNA accessibility, whereas non‐responders show negligible changes in accessibility following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this differential response to HDACi treatment is related to individual variation in chromatin accessibility. For example, in clinical studies testing the efficacy of HDACi drugs as cancer treatments, the pattern of transcription factor occupancy in cells from individual T‐cell lymphoma patients predicts HDACi treatment efficacy . In responsive patients, HDACi treatment is correlated with a rise in DNA accessibility, whereas non‐responders show negligible changes in accessibility following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…13 Responses were found to be strongly associated with concurrent gains in chromatin accessibility. 13 Responses were found to be strongly associated with concurrent gains in chromatin accessibility.…”
Section: Predictive Biomarkers?mentioning
confidence: 96%
“…Qu et al recently described the chromatin accessibility profiles of CTCL and analyzed the dynamic changes associated with HDACi response and resistance. 13 Responses were found to be strongly associated with concurrent gains in chromatin accessibility. Such profiling assays could be analyzed as predictive biomarkers in future studies.…”
Section: Predictive Biomarkers?mentioning
confidence: 96%
“…For example, researchers have shown that the T cells of the immune system change at the epigenomic level during aging or functional exhaustion 4,5 . The response of certain cancer patients to a drug treatment can be predicted from DNA accessibility of target loci during treatment 6 . Whether a person smokes cigarettes, and thus may be at risk for myriad cancers, can be inferred from DNA methylation patterns 7 .…”
Section: To the Editormentioning
confidence: 99%